2022
DOI: 10.14202/vetworld.2022.775-781
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of leptin gene (single nucleotide polymorphisms c.73T>C) and its association with body weight and body measurements in Madura cattle

Abstract: Background and Aim: Madura cattle is local cattle in Indonesia. This cattle hasphenotypic variations in growth traits. This study aimed to identify leptin (LEP) gene polymorphism exon 2 associated with body measurements in Madura cattle. Materials and Methods: We recorded body weight (BW) and body measurements of 51 Madura cattle aged 1-4 years in Waru District, Madura. The LEP gene genotyping was conducted using the polymerase chain reaction-restricted fragment length polymorphism method with AciI restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Kawaguchi et al (2017) reported a significant association between the genotype of Japanese Black and growth. Kuswati et al (2022) reported that this SNP was significantly associated with body weight and body measurements. In addition, the leptin gene has been reported to affect fertility and production characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Kawaguchi et al (2017) reported a significant association between the genotype of Japanese Black and growth. Kuswati et al (2022) reported that this SNP was significantly associated with body weight and body measurements. In addition, the leptin gene has been reported to affect fertility and production characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Several Leptin and its receptor gene polymorphism studies have been carried out to study the variation of different productivity taris across groups (Raza et al, 2020) [9] . A polymorphism study in exon 2 of LEPR gene in Madura cattle has been found to be associated with body weight (Kuswati et al, 2022) [5] . However, few SNP variations and point mutations are deleterious in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Since livestock producers in Indonesia rely heavily on cattle for their revenue, cattle are one of the most essential livestock products (Dakhlan et al, 2022;Kuswati et al, 2022;Pakpahan et al, 2022;Prihandini et al, 2022;Sudrajad et al, 2022). The productivity of Indonesian livestock, especially local cattle, is still relatively low and is a major problem that must be resolved immediately (Mayulu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%